Simplification of Brackets

There is no content available!

To Access the full content, Please Purchase

  • Q1

    [(-8) + 7)] ÷ [(-11) + 10] = ……

    Marks:1
    Answer:

    1

    Explanation:

    [(–8) + 7)] ÷ [(–11) + 10]

    = (–1) ÷ (–1)

    = 1

    View Answer
  • Q2

    [8 +{ 5 –(4 3 -7) -5 +3 4} +9] = …

    Marks:1
    Answer:

    24.

    Explanation:

    By using the rule of Bodmas.
    [8 +{ 5 –(4 3 -7) -5 +3 4} +9] = [8 + {5 –(12-7) -5 + 3 4} +9]
    = [8 + {5 – 5 - 5 + 12} + 9]
    = [8 + {12 - 5} + 9]
    = [8 + 7 + 9]
    = [15 + 9]
    = 24

    View Answer
  • Q3

    7 – [13 – {–2 – 6 (6 of –5)}]

    Marks:1
    Answer:

    172

    Explanation:

    7 – [13 – {–2 – 6 (6 of –5)}]

    = 7 – [13 – {–2 – 6(–30)}] = 7 – [13 – {–2 + 180)}]

    = 7 – [13 + 2 – 180] = 7 - [15-180]= 7 - [-165]= 7 + 165 = 172

    View Answer
  • Q4

    Value of 124 × 4 – 3 + 118 ÷ 2 is

    Marks:1
    Answer:

    552

    Explanation:
    124 × 4 – 3 + 118 ÷ 2
    = (124 × 4) –3 + 59
    = 496 – 3 + 59
    = 555 – 3
    = 552
    View Answer
  • Q5

    The sum of [(+70) + (–48)] is

    Marks:1
    Answer:

    22

    Explanation:

    [(+70) + (–48)]

    = +70 – 48

    = 22

     

    View Answer